2021
DOI: 10.1136/bmjqs-2021-013311
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centred outcomes of imaging tests: recommendations for patients, clinicians and researchers

Abstract: BackgroundImaging tests are one of the most frequently used diagnostic modalities in healthcare, but the benefits of their direct impacts on clinical decision-making have been countered by concerns that they can be overused. Assessing the relative value of imaging tests has largely focused on measures of test accuracy, which overlooks more comprehensive benefits and risks of imaging tests, particularly their impact on patient-centred outcomes (PCOs). We present the findings of the Patient Reported Outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Perhaps this neglect is somehow related to PCOs still currently being in its early stages—at least in the field of the clinical evaluation of AI in medicine. The first comprehensive attempt to define the PCOs of imaging tests, to which the majority of AI tools currently available after regulatory approval belong, was made only recently [ 30 ]. According to a recent systematic evaluation of research protocols for clinical trials for AI technology registered in ClinicalTrials.gov up to 2022 by Pearce et al [ 88 ], the use of PROMs in the assessment of AI health technologies as trial endpoints was observed in only 7% of clinical trials for AI technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps this neglect is somehow related to PCOs still currently being in its early stages—at least in the field of the clinical evaluation of AI in medicine. The first comprehensive attempt to define the PCOs of imaging tests, to which the majority of AI tools currently available after regulatory approval belong, was made only recently [ 30 ]. According to a recent systematic evaluation of research protocols for clinical trials for AI technology registered in ClinicalTrials.gov up to 2022 by Pearce et al [ 88 ], the use of PROMs in the assessment of AI health technologies as trial endpoints was observed in only 7% of clinical trials for AI technology.…”
Section: Discussionmentioning
confidence: 99%
“…Questions related to insurance coverage were designed in alignment with the National Health Insurance of the ROK. To address potential unfamiliarity with PCOs among some respondents, we provided a concise and explicit explanation of PCOs in the survey, focusing particularly on PCOs as related to imaging tests (Section B of survey questionnaire in Supplements ) [ 30 ]. Furthermore, to avoid confusion among the respondents, the survey also included explanations of the four value elements provided by AI, as outlined in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This illustrates the considerations that patients go through with weighing the advantages and disadvantages of diagnostic tests. 24…”
Section: Main Findingsmentioning
confidence: 99%